DNA barcoding of seven cyprinid fish species in the Iraqi Inland waters using mitochondrial COI gene sequence (Baghdad Science Journal, 2024)
Family Cyprinidae is the largest fish family in the Iraqi inland waters. The cyprinid fish species were described by traditional biometry. Family Cyprinidae fish species in Iraq are important because of ecological and economic aspects. While the morphological similarity among the cyprinid species made the identification not easy.  DNA barcoding was chosen to confirm the taxonomy and ensure genetic diversity. Seven cyprinid fish species, Luciobarbus barbulus, L. xanthopterus, L. kersin, L. esocinus, Arabibarbus grypus, Cyprinus carpio, and Acanthobrama marmaid were collected from the Shatt Al-Arab River, the Marshes, and the Mosul Dam reservoir. The mitochondrial Cytochrome C Oxidase gene of the specimens was amplified and sequenced. Universal primers were chosen for this purpose. Chromas software was used for processing the sequences. The result showed that the sequence ranged from 600-657 bp. While the neighbor-joining tree created by Clustal Omega software revealed the four Luciobarbus species clustering into two central branches, while the other three diverged. Nucleotide distribution statistically for the studied fish species was compared. The results of DNA barcoding using COI gene sequence proved the four independent Luciobarbus fish species. The COI gene sequence was successful as a DNA barcode which is accurate in species identification. The sequences were deposited in the gene bank under OM669701, OM669699, OM669702, OM669705, OM669700, OM669703 and OM669704. This study represents the starting line for the DNA barcoding project to detect all fish fauna sequences in the Iraqi inland waters. In addition, it will be very useful in the conservation program of native species in Iraqi inland waters.